2008
DOI: 10.1038/ijir.2008.24
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem, confidence and relationship satisfaction in men with erectile dysfunction: a randomized, parallel-group, double-blind, placebo-controlled study of sildenafil in Mexico

Abstract: Erectile dysfunction (ED) negatively impacts self-esteem and relationship satisfaction. The Self-Esteem and Relationship (SEAR) questionnaire is a validated, ED-specific, patient-reported instrument that specifically addresses self-esteem and relationship issues within the context of ED. Effective ED treatment with sildenafil in a double-blind, placebo-controlled clinical trial conducted in Brazil, Mexico, Australia and Japan showed pooled cross-cultural improvements in self-esteem, confidence and relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…There were 28 single‐ or double‐blind, placebo‐controlled, parallel‐group trials [9,16,20–45], one treatment‐controlled, parallel group trial [46], and three open‐label trials [15,47,48]. In addition, there were five pooled analyses of RCT data [14,49–52] and three secondary or subgroup analyses of RCT data [53–55].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 28 single‐ or double‐blind, placebo‐controlled, parallel‐group trials [9,16,20–45], one treatment‐controlled, parallel group trial [46], and three open‐label trials [15,47,48]. In addition, there were five pooled analyses of RCT data [14,49–52] and three secondary or subgroup analyses of RCT data [53–55].…”
Section: Resultsmentioning
confidence: 99%
“…All publications reported that men had ED for at least 6 months (where relevant), and most men had ED for at least 3 years (Tables and ). Disease duration was not reported as an eligibility criterion for 24 of the 40 publications [9,14,21,23,25–33,41,43,44,47–49,51–55]. The mean age of men with ED varied from 45 to 62 years [21,26], and most had ED of mixed or organic etiology [9,14,15,20–22,24–29,32–41,44,46–48,50–53,55,71].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is clear evidence that sildenafil is efficacious in the treatment of the broad population of men with erectile dysfunction when taken on demand at a doses of 25, 50, and 100 mg. There are multiple level 1 studies with consistent outcomes [20–43]. The overall grade of recommendation is grade A.…”
Section: Drugs Which Are Effective When Administered Systemicallymentioning
confidence: 99%
“…Although side effects do occur with sildenafil (most notably headache, flushing, indigestion, nasal congestion, and occasional visual changes), providing that the drug is used in line with the labeling recommendations, there is no convincing evidence in the literature of any significant safety issue, including cardiovascular, visual, and aural safety [20–74] (Consistent level 1 studies, Overall grade of recommendation is grade A).…”
Section: Drugs Which Are Effective When Administered Systemicallymentioning
confidence: 99%